NAMPT Inhibition Induces Neuroblastoma Cell Death and Blocks Tumor Growth - Vallejo, Frederic A.; Sanchez, Anthony; Cuglievan, Branko; Walters, Winston M.; De Angulo, Guillermo; Vanni, Steven; Graham, Regina M. (Frontiers in Oncology, 2022)
High-risk neuroblastoma (NB) portends very poor prognoses in children. Targeting tumor metabolism has emerged as a novel therapeutic strategy. High levels of nicotinamide-adenine-dinucleotide (NAD+) are required for rapid cell proliferation. Nicotinamide phosphoribosyl transferase (NAMPT) is the rate-limiting enzyme for NAD+ salvage and is overexpressed in several cancers. Here, we determine the potential of NAMPT as a therapeutic target for NB treatment. NAMPT inhibition cytotoxicity was determined by trypan blue exclusion and LDH assays. Neuroblastoma stem cell self-renewal was evaluated by neurosphere assay. Protein expression was evaluated via Western blot. The effect of targeting NAMPT in vivo was determined using an NB1691-xenografted mouse model. Robust NAMPT expression was demonstrated in multiple N-MYC amplified, high-risk neuroblastoma cell lines. NAMPT inhibition with STF-118804 (STF) decreased ATP, induced apoptosis, and reduced NB stem cell neurosphere formation. STF treatment down-regulated N-MYC levels and abrogated AKT activation. AKT and glycolytic pathway inhibitors in combination with NAMPT inhibition induced robust, greater-than-additive neuroblastoma cell death. Lastly, STF treatment blocked neuroblastoma tumor growth in mouse xenograft models. NAMPT is a valid therapeutic target as inhibition promoted neuroblastoma cell death in vitro and prevented tumor growth in vivo. Further investigation is warranted to establish this therapy’s role as an adjunctive modality.